Advances in the emerging gradient designs of Li metal hosts - Guan, Wanqing (2023)
Developing host has been recognized a potential countermeasure to circumvent the intrinsic drawbacks of Li metal anode (LMA), such as uncontrolled dendrite growth, unstable solid electrolyte interface, and infinite volume fluctuations. To realize proper Li accommodation, particularly bottom-up deposition of Li metal, gradient designs of host materials including lithiophilicity and/or conductivity have attracted a great deal of attention in recent years. However, a critical and specialized review on this quickly evolving topic is still absent. In this review, we attempt to comprehensively summarize and update the related advances in guiding Li nucleation and deposition. First, the fundamentals regarding Li deposition are discussed, with particular attention to the gradient design principles of host materials. Correspondingly, the progress of creating different gradients in terms of lithiophilicity, conductivity, and their hybrid is systematically reviewed. Finally, future challenges and perspective on the gradient design of advanced hosts towards practical LMAs are provided, which would provide a useful guidance for future studies.